(3cf fLeG (B:s (3QMdI Gdi GcJTGa GdPGJ hGdeQhfI GdfaSjI (B/s - (3CHh YSdj(B, (3efis ((3GdTGQbI (B- (3GdGeGQGJ(B:s (3GHgGQ ddJhRjY hGdfTQ(B,s, 2024)
(3cJGH ebGdj ZQVg Cf jchf Odjdc GdJMhjdj dGcJTGa GdPGJ hGdeQhfI(B. (3OGNd UaMGJg, SJHOC QMdI bhjI ef GdhYj GdPGJj, hJWdb GdYfGf dTZac hgOac(B. (3JYde cjajI GdJZdH Ydi JMOjGJ GdMjGI HYbdjI Gdfeh hJfejI GdbhI ddJZdH Ydi GdTOGFO(B. (3GHMK Yf GdeJYI aj GdCTjGA GdHSjWI, hbe HHfGA YdGbGJ UMjI, hGNdb MjGI edjFI HGdEjLGHjI(B.s
Keywords: (3JWhjQ GdPGJ(B.s